Determinants of Behavioral Aspects Related to Blood Sugar Levels of Type II Diabetes Mellitus Patients in the Working Area of the Banjar Baru Health Center, Tulang Bawang Regency - Nurul Aziza; Nova Mega Rumana; Radella Hervidea; Dewi Woro Astuti; Adhi Nurhartanto (International Journal Labs, 2025)
Diabetes mellitus tipe II is a chronic disease characterized by high blood glucose levels due to insulin resistance or insufficient insulin production. This study aims to determine behavioral determinants related to blood glucose levels in diabetes mellitus tipe II patients. This research used a cross-sectional survey analytic design with 83 diabetes mellitus tipe II patients as respondents in the working area of Banjar Baru Health Center, Tulang Bawang Regency. Data were collected through questionnaires and blood glucose measurements. Data analysis used univariate, bivariate (chi-square), and multivariate (logistic regression) analyses. The results showed that 55.4% of patients had abnormal blood glucose levels (>200 mg/dl). Bivariate analysis revealed significant relationships between knowledge (p=0.005; OR=4.34), attitude (p=0.000; OR=9.717), age (p=0.009; OR=4.545), abdominal obesity (p=0.000; OR=5.143), physical activity (p=0.000; OR=5.903), and dietary patterns (p=0.000; OR=9.72) with blood glucose levels. Multivariate analysis showed that dietary patterns were the most dominant factor (p=0.020; OR=10.946) after controlling for attitude, obesity, and physical activity variables. Diabetes mellitus tipe II patients with irregular dietary patterns have a 10.946 times higher risk of experiencing elevated blood glucose levels compared to those with regular dietary patterns.